1999
DOI: 10.1046/j.1365-2656.1999.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of conspecific reproductive success for breeding habitat selection in a non‐colonial, hole‐nesting species, the collared flycatcher

Abstract: Summary1. Breeding habitat quality strongly aects ®tness. Therefore, individuals are likely to select their breeding habitat after gathering information on quality of potential breeding patches. In the study reported in this paper, we investigated whether local reproductive success of conspeci®cs in a patch (patch reproductive success, PRS) could be used to assess habitat quality and make dispersal decisions in a non colonial, hole-nesting, passerine bird, the collared¯ycatcher (Ficedula albicollis). 2. Assump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
167
3
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 164 publications
(182 citation statements)
references
References 60 publications
11
167
3
1
Order By: Relevance
“…Tree Sparrows clearly select nests that hatched nestlings, no matter whether they are successful or not, and avoid nests deserted during their construction, egg laying, or incubation, (mostly due to human interference -see Pinowski et al 1973). This is in agreement with other studies that indicate that for adults the experience from the breeding season is a basic cue for selection of a suitable nest site in autumn (Doligez et al 1999). Only 16% of Tree Sparrows during the period of spring courtship selected the same nest-boxes as in the period of autumnal display, because of: 1 st : winter mortality is very high (ca.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Tree Sparrows clearly select nests that hatched nestlings, no matter whether they are successful or not, and avoid nests deserted during their construction, egg laying, or incubation, (mostly due to human interference -see Pinowski et al 1973). This is in agreement with other studies that indicate that for adults the experience from the breeding season is a basic cue for selection of a suitable nest site in autumn (Doligez et al 1999). Only 16% of Tree Sparrows during the period of spring courtship selected the same nest-boxes as in the period of autumnal display, because of: 1 st : winter mortality is very high (ca.…”
supporting
confidence: 92%
“…Doligez et al 1999, Reed et al 1999, Danchin et al 2001, we classified Tree Sparrows nests from the immediately previous breeding season according to the most advanced stage of development, regardless of brood timing. Thus, any nesting attempt with unhatched eggs or dead nestlings was disregarded if a subsequent attempt in the same box was successful in the same season.…”
mentioning
confidence: 99%
“…Therefore, parental activity around a nest is a good predictor of the reproductive success at fledging at that specific breeding site in the current year. Because reproductive success is locally temporally autocorrelated (Doligez et al 1999), parental activity should also predict success at this site in the next year.…”
Section: Resultsmentioning
confidence: 99%
“…Although some other factors can also be involved in emigration, there is extensive evidence that breeding failure can have an important influence (e.g. Danchin et al 1998;Doligez et al 1999;. 1974 1977 1980 1983 1986 1989 1992 1995 1998 Results showed that age also influenced emigration to other local populations .…”
Section: Discussionmentioning
confidence: 99%